A multidisciplinary approach to calibrating advanced numerical simulations of masonry arch bridges. (15th August 2019) - Bautista-De Castro, Álvaro; Sánchez-Aparicio, Luis Javier; Carrasco-García, Pedro; Ramos, Luís F.; González-Aguilera, Diego
Highlights: A non-destructive experimental campaign for masonry arch bridges is presented. The MASW method allowed to characterize the mechanical properties of the infills. A multidisciplinary method was used to create an accurate numerical model. The PCE metamodel identified the most sensitive variables of the numerical model. Abstract: This paper proposes a robust multidisciplinary method that combines geomatic procedures (terrestrial laser scanning and reverse engineering), geophysical methods (ground-penetrating radar and multichannel analysis of surface waves), sonic and impact echo tests, and ambient vibration approaches to generate accurate numerical simulations of masonry arch bridges. These methods are complemented by a robust finite element model updating method based on metamodeling global sensitivity analysis and a robust calibration strategy. The results obtained corroborate the feasibility of the proposed methodology with an average relative error in frequencies of 1.21% and an average modal assurance criterion of 0.93.